Contributions in pediatric nursing care teenager person in middle stage - González Zúñiga, Sophía (2016)
Introduction. Accompaniment to the adolescent described in intermediate stage through a program of Pediatric Nursing in an institution of secondary education in 2014, whose main objective was to articulate the need for knowledge about safe sex and prevention of drug use. There is an urgent need to improve care coverage because the first level of care is the foundation of the health system and is considered as the ideal space to carry out the intervention with the adolescent population.Method. The program was developed under the constructivist and participative methodology, using strategies: "Interview of the adolescent" for individual approach and "workshops" for the group approach.Result. Throughout the program active participation by the population, was found the situation required greater approach by Pediatric Nursing in eating habits; in each activity we started from the basic knowledge they possessed adolescents, the program seemed interesting and exceeded their expectations.Conclusion. It was concluded that the lines of action raised, individual and group showed different aspects of adolescence needed to get a complete picture of the person and thus provide a more accurate approach; the criterion of professional pediatric nursing is essential to meet the identified needs and characterization of risk factors and / or protective.